Meniti duri dan ranjau: Pembikinan gender dan seksualiti dalam konteks dunia melayu - Ruzy Suliza Hashim, (Universiti Kebangsaan Malaysia, 2006)
This article explores the construction of gender and sexuality in the context of the Malay world. Drawing on the perspectives of biological theory, psychodynamic theory and cultural theory, each viewpoint is deliberated and discussed. However, it is also argued that formation of sexual identity is largely attributed to what is learnt, copied and regulated by societal and religious demands. Using the examples from the Malay world, it is clear that slippages between the official code and the lived realities of men and women contribute to inequity of gender relations